DEVELOPMENT OF LIBRARY CENTRES IN STRUCTURE OF YEKATERINOSLAV EDUCATION INSTITUTIONS - Luchka, Liudmyla M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article shows the contribution of educational institutions‘ leaders to Yekaterinoslav librarianship in the second half of the 19th – the beginning of the 20th centuries. The article describes some aspects of library activity such as book acquisition and student reading guidance which were of great interest on Pedagogical councils.